(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
The Church of the Eremitani in Padua is a place of undeniable cultural and historical value, and a popular tourist destination, its principal attraction being the famous cycle of frescoes dedicated to the stories of Saint James and Saint Christopher in the Ovetari Chapel (1448–1457). Work on the frescoes was begun in 1448 by a group of artists including a very young Andrea Mantegna. The artistic value of the chapel as a document of Renaissance painting, and as a testimony of the experiments in perspective undertaken by Mantegna in those years, is a widely studied subject but it is worth remembering the peculiarity of this work: parts of it are missing. Substantial gaps were left following the bombing raids of the Second World War, the frescoes later undergoing a difficult process of restoration. What the visitor can admire today is a partial reconstruction of the frescoes that aims to narrate the missing parts rather than offer the (perhaps impossible) reassembly of the thousands of fragments collected. A recent study, which was launched with support from the European Social Fund, has reopened the debate on the methods of preserving and displaying historical artefacts in light of the possibilities offered by new digital technologies. Designing a tool that can be used by anyone, in this case a multimedia app for users who are mostly of school age, involves the examination of its educational and communicative potential, including the ability to share multimedia material quickly and easily. The development of the app provides an opportunity to reflect on the power of images imposed on us by the dynamics of the modern world, but also allows us to consider how these technologies can re–establish a relationship between the visitor and the work of art in an emblematic place, for example using ‘virtual’ versions of the frescoes by Mantegna.